The effect of financial leverage on firm performance: a study on the plantation companies in Malaysia / Siti Norhawa Rosli - Rosli, Siti Norhawa (2019)
The purpose of this study is to determine the relationship between financial leverage and firm's performance of the plantation industry in Malaysia. Therefore, the financial leverage is expected to have an impact on its firm's performance. In addition, while corporate governance studies are increasing, only a few studies have considered plantation companies. This study intends to address these research issues by investigating the effect of financial leverage on firm performance using a number of Malaysian plantation companies. This study aims to determine whether financial leverage has an impact on firm's performance. To achieve the research objective, a 5 year data of 30 Malaysian plantation companies was analyzed using Panel data. Results of this study showed that there was a positive relationship between financial leverage and firm performance.